2019
DOI: 10.1177/0038026119876775
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating vulnerability: The experience of long-term social security recipients

Abstract: This article addresses the prominence of ‘vulnerability’ as a way of making sense of disadvantage and suffering in both social policy and social science. It examines the interplay of vulnerability as a material phenomenon and cultural script by foregrounding the experiences of the most marginal benefit claimants in Australia’s residual social security system. The article questions whether the everyday disruptions and challenges that unsettle yet settle-into life in poverty are intelligible within authorised id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…We are reacting on two trends in literature on vulnerability. The first one focuses on deprivation, marginalization, disadvantage, poverty and social problems [49]. Doctors cannot be attributed to this group.…”
Section: Discussionmentioning
confidence: 99%
“…We are reacting on two trends in literature on vulnerability. The first one focuses on deprivation, marginalization, disadvantage, poverty and social problems [49]. Doctors cannot be attributed to this group.…”
Section: Discussionmentioning
confidence: 99%
“…Andres and Round, 2015; Hall, 2016; Patrick, 2017) and manage the stigma and trauma associated with poverty (e.g. McKenzie, 2015; Mitchell, 2020; Shildrick and MacDonald, 2013).…”
Section: Agency Coping and Resiliencementioning
confidence: 99%
“…Ethnographic research in impoverished neighbourhoods or housing estates in particular has shown how structures of family and community care provide practical resources in times of struggle and a source of purpose and pride (McKenzie, 2015; Smith, 2017). However, coping is not inherently constructive or successful; it can come at the cost of health (Harrison, 2012), social capital (McKenzie, 2015), time and emotional strain (Patrick, 2017), dignity (Mitchell, 2020), debt (Marston and Shevellar, 2014) and destructive behaviour towards self or others (Hoggett, 2001).…”
Section: Agency Coping and Resiliencementioning
confidence: 99%
See 2 more Smart Citations